Relationship between Zingiberaceae Leaves Compounds and its Tyrosinase Activity - Batubara, Irmanida; Kartika, Yuni; Darusman, Latifah K (Biosaintifika: Journal of Biology & Biology Education, 2016)
The leaves of Zingiberaceae family has not been much explored its potential, especially as a skin lightening. The relationship between total anthocyanins, chlorophyll, carotenoids and tannins contents of Zingiberaceae leaves and tyrosinase activity were determined. Ten species of Zingiberaceae were separated by n-hexane and the residues were extracted with ethyl acetate. The total anthocyanins, chlorophyll, carotenoids, tannins contents and the activities of ethyl acetate extracts were determined by spectrometric method. The tyrosinase inhibition was determined by using L-tyrosine (monophenolase) and L-DOPA (diphenolase) substrates. The most active extract was the leaves extract of Zingiber purpureum which exhibited 82.86% for monophenolase inhibition and the leaves extract of Curcuma zedoaria which exhibited 90.20% for diphenolase inhibition. The correlation between carotenoids content and monophenolase inhibition was 52%, while between tannin content and diphenolase inhibition was only 15%. Therefore, among 10 leaves species of Zingiberaceae, Zingiber purpureum Roscoe and Curcuma zedoaria leaves are the most potential for tyrosinase inhibitors and can be developed as whitening agent.How to CiteBatubara, I., Kartika, Y. & Darusman, L. K. (2016). Relationship between Zingiberaceae Leaves Compounds and its Tyrosinase Activity. Biosaintifika: Journal of Biology & Biology Education, 8(3), 371-377.